PsycEXTRA Dataset 2004
DOI: 10.1037/e741702011-001
|View full text |Cite
|
Sign up to set email alerts
|

Competency Based Future Leadership Requirements

Abstract: Public reporting burden for this collection of information is estimated to average lliour per response, Including the time for reviewing instaictlons, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regardng this burden estimate or any other aspect of this coUection of information, including suggestions for reducing this burden to Department of Defense, Washington HeaAguartens Services, Diractorata for Inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…Each of the competencies is further described by secondary components, presented in Table 3, and sample actions for each component (see Horey et al, 2004). The model was developed from several sources, including Army leadership doctrine, reviews of competency and leadership literature, and input from subject matter experts.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the competencies is further described by secondary components, presented in Table 3, and sample actions for each component (see Horey et al, 2004). The model was developed from several sources, including Army leadership doctrine, reviews of competency and leadership literature, and input from subject matter experts.…”
Section: Model Descriptionmentioning
confidence: 99%
“…This effort resulted in the development of a core leader model which is described in terms of eight competencies, 55 components, and over 200 sample actions and behaviors (Horey, Fallesen, Morath, Cronin, Cassella, Franks, & Smith, 2004). A series of research efforts were recently concluded to establish evidence of validity of the model and identify situational variations in the model.…”
mentioning
confidence: 99%
“…The Leadership Requirements Model has been through a series of research-based studies that have demonstrated its reliability and validity. Its conceptualization began with the identification of future leader requirements (Horey, Fallesen, Morath, Cassella, Franks, & Smith, 2004). Actual validation was accomplished via Horey, Harvey, Curtin, KellerGlaze, Morath, & Fallesen (2006, April).…”
Section: Leadership Assessmentmentioning
confidence: 99%
“…Although the need for influence skills and interpersonal adaptability in the Army environment has been well established (Department of the Army, 2001;Horey, Fallesen, Morath, Cronin, Cassella, Franks, & Smith, 2004;Wong, Gerrars, Kidd, Pricone, & Swengros, 2003), little formal training exists to help new Army leaders enhance these skills. To address this gap, the Army Research Institute's Leader Development Research Unit (ARI-LDRU) has recently initiated work on the Army Technology Objective (ATO) titled Accelerating Leader Development.…”
mentioning
confidence: 99%